Cognitive Function and the Ageing Process: The Peculiar Role of Mild Thyroid Failure - Pasqualetti, Giuseppe; Caraccio, Nadia; Dell`Agnello, Umberto; Monzani, Fabio (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2016)
Background: Over the last decades an increasing body of evidence suggested a possible relationship between thyroid hormone (TH) and the ageing process, and several efforts have been made to determine the actual role of TH dynamic during human life. It is still unclear whether the serum level shift of Thyroid Stimulating Hormone toward higher value, observed during ageing, is a normal adaptive response associated with senescence or an actual mild thyroid dysfunction. A growing body of evidence supports the hypothesis of a reset of the hypothalamus-pituitary-thyroid axis in order to contrast the catabolic status of the ageing process. On the other hand, several meta-analyses showed a direct link between subclinical hypothyroidism (sHT) and cardiovascular events (both ischemic heart disease and stroke), although mainly in individuals younger than 65 years. Similarly, a recent meta-analysis documented consistent data on a positive relationship between sHT and cognitive impairment, but only in individuals younger than 75 years. Conclusion: The available data suggest a complex relationship between mild thyroid failure and the ageing process as well as the development and progression of several cardiovascular and neurological diseases. In this paper, we reviewed the scientific English literature on sHT and the ageing process focusing on experimental evidences related to cognitive impairment and dementia. Moreover, we focused on new patents of treatments potentially able to improve the care of sHT patients, especially in the elderly, where treatment drawbacks may have negative impact on the long term outcome.
Keywords: dementia